Corporate Governance Reform in Banking: Risk Governance and Performance of Commercial Banks in Asia Emerging Markets - Hasroleffendy Hassan; Abdul Hadi bin Zulkafli; Hasindar Ibrahim (International Journal of Supply Chain Management, 2019)
The banking institutions worldwide, including banks in emerging Asia have been operating in more challenging and more uncertain environment after the 2007 financial calamity. In ensuring an optimal functioning of the banking sector, Basel Committee on Banking Supervision (BCBS) highlighted the importance of effective corporate governance in the banking sector. Observing from the suggestion for banks to reform their corporate governance, this study is conducted to examine the relationship between risk governance mechanism and bank performance. Using a sample of 109 banks with 545 observations in eight Asia emerging economies for a period of 2011-2015, it is evidenced that risk governance mechanism is significantly and positively related with bank performance represented by its liquidity. Therefore, risk governance is vital for banks betterment in Asia emerging market to weather future negative effects as well as to restore and maintain their resilience.